PEMENUHAN HAK RESTITUSI KEPADA KORBAN TINDAK PIDANA PERSETUBUHAN: (Studi Putusan Nomor: 26/Pid.Sus/2023/PN.Tbn) - Sari, Linda Purnama; Serbabagus, Shalahudin (LAW Specialist Jurnal Ilmiah Hukum, 2024)
Children are a mandate from God so we must protect and uphold the rights of others, but lately there have been many cases related to criminal acts involving children, where children become victims of criminal acts, especially sexual violence. The National Commission on Child Protection (Komnas PA) report states that in 2023 there were 3,547 complaints of cases of violence against children, with 1,915 cases of sexual violence. The legal issue raised is the imbalance of legal protection between perpetrators and victims of criminal offences. Although the 1945 Constitution states the equal status of citizens before the law, in practice, victims’ rights such as compensation are still difficult to fulfil. In addition, the concept of punishment in the Criminal Code (KUHP) tends to favour the perpetrators of criminal acts. This research aims to analyse the legal protection of children as victims of sexual violence, and the judge’s decision in imposing the law on the perpetrator and identifying the obstacles faced in the process of fulfilling the rights of victims, one of which is restitution. The research method used is juridical-normative with a statutory, conceptual, and case approach. The results showed that the legal protection of children as victims of sexual violence is not optimal. There are several obstacles, among others: 1. limited understanding of law enforcement officials on victim protection; 2. lack of budget and facilities to fulfil victims’ rights; 3. low public awareness to report cases of sexual violence against children. 4. The low awareness of the public regarding the demand for restitution to the perpetrators of these crimes. Therefore, efforts are needed to improve the relevant laws and regulations, increase the capacity of law enforcement officials, and strengthen community participation in child protection.